Prescribing at a glance - Ross, Sarah (Clinical pharmacologist) (At a glance series (Oxford, England), 2014)
The principles of drug therapies are fundamental to medical practitioners in all branches; but are often difficult to get to grips with. Prescribing at a Glance addresses the most common uses of prescription drugs, and follows progress from dose calculation, administration to monitoring the effects in the treatments of major presenting problems. With a focus on prescribing, this user-friendly guide helps practitioners to develop crucial knowledge and skills, including establishing accurate drug histories, planning appropriate therapies, writing safe and legal prescriptions